Regularities of Macroscopic Localization of Plastic Deformation in the Stretching of a Low-Carbon Steel; Russian Physics Journal; Vol. 57, iss. 3 - Barannikova S. A.; Kosinov D. A.; Nadezhkin M. V. Mikhail Vladimirovich; Lunev A. G. Alexey Gennadievich; Gorbatenko V. V.; Zuev L. B.; Gromov V. E. (2014, 2014)
Title screen